Interactive video-based flipped classroom on student motivation and learning participation in islamic religious education - Zul Anwar; Hidayatullah Hidayatullah (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
The integration of digital learning strategies in Islamic Religious Education is essential to meet the evolving educational demands of the digital era. This study investigates the effectiveness of an interactive video-based flipped classroom model in enhancing student motivation and learning participation among junior high school students. Rooted in the ARCS motivation model and engagement theory, the study adopts a quasi-experimental design using a Nonequivalent Control Group. A total of 60 eighth-grade students from Central Lombok, Indonesia, were divided into two groups: one experienced the flipped classroom with interactive video, and the other followed conventional instruction. Data were collected through validated motivation questionnaires and observation checklists based on Reeve & Tseng’s engagement indicators. Statistical analyses, including descriptive statistics and independent samples t-tests, were conducted to examine differences in outcomes. Findings show that students in the flipped classroom group exhibited significantly higher levels of motivation and learning participation compared to the control group. The most notable gains appeared in the “Confidence” dimension of motivation and across all four engagement types—behavioral, emotional, cognitive, and agentic. The use of interactive videos allowed for better attention capture, relevance to students’ lives, and deeper reflective learning in religious contexts. These results affirm that an interactive video-based flipped classroom is not only pedagogically effective but also particularly suitable for value-oriented subjects like Islamic Religious Education. It supports a shift toward more reflective, participatory, and spiritually engaging learning processes.